2021
DOI: 10.1039/d1ra04195a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design approaches to optimize ultrasound-assisted simultaneous-silylation dispersive liquid–liquid microextraction for the rapid determination of parabens in water samples

Abstract: This work describes a rapid solvent-minimized process to effectively determine four common paraben preservatives (methyl-, ethyl-, propyl- and butyl-paraben) in surface water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The detection of parabens in vegetable oil 24 samples was performed by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) which is more sensitive than HPLC-UV; however, the LODs were similar to those obtained in our method. Hsieh et al 7 also reported low LOD values in DLLME of parabens from water samples. However, our method is superior in terms of extraction time and precision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of parabens in vegetable oil 24 samples was performed by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) which is more sensitive than HPLC-UV; however, the LODs were similar to those obtained in our method. Hsieh et al 7 also reported low LOD values in DLLME of parabens from water samples. However, our method is superior in terms of extraction time and precision.…”
Section: Resultsmentioning
confidence: 99%
“…However, these chemicals have some health and safety concerns associated with them including increasing the risk of cancer, skin irritation, and environmental pollution upon accumulation in either the human body or the environment. 1 Among different analytical methods [2][3][4][5][6][7][8] that have been employed for the extraction and/or purification of parabens from a diverse range of real matrices, liquid-liquid microextraction is the most used technique. This technique provides a fast and simple extraction of the target compounds from their origins.…”
Section: Introductionmentioning
confidence: 99%
“…Personal care products have been detected in various environmental matrices and identified as emerging pollutants 1 that also pose a threat to organisms. 2 , 3 As the components of personal care products and food additives, flavors are also widely used in food production, such as biscuits, frozen foods, condiments, canned foods, and beverages. 4 Recent studies have found that flavors were also detected in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Personal care products have been detected in various environmental matrices and identified as emerging pollutants that also pose a threat to organisms. , As the components of personal care products and food additives, flavors are also widely used in food production, such as biscuits, frozen foods, condiments, canned foods, and beverages . Recent studies have found that flavors were also detected in aquatic environments. , Most of the cosmetics contain flavors that often enter the environment through common ways, such as washing , and swimming, and some flavors are also mixed with antibiotics, steroids, anti-inflammatory drugs, sedatives, and diet pills .…”
Section: Introductionmentioning
confidence: 99%